Kecenderungan Trust Issue pada Remaja Korban Bullying - Nur Hidayat , Erwin Kurniawan; Amalia, Ulfa; Rossydah, Soffa (Universitas Palangka Raya, 2026)
Bullying is an aggressive behavior that has a profound impact on the psychological condition of victims, including the emergence of trust issues or difficulties in trusting others. This study aims to describe the forms and impacts of trust issue tendencies among adolescents who have experienced bullying. A qualitative approach with a case study method was employed involving five adolescents aged 16–18 years in Yogyakarta who had experienced verbal and social bullying. Data were collected through in-depth interviews and analyzed using data reduction, data presentation, and conclusion drawing techniques. The findings reveal that traumatic bullying experiences lead to anxiety, fear, difficulty forgiving, and tendencies to withdraw from social interactions. These conditions contribute to decreased self-confidence and diminished quality of interpersonal relationships. The study concludes that bullying significantly influences the formation of trust issues among adolescents, highlighting the need for psychological assistance and a supportive environment to facilitate recovery. Furthermore, trust issues not only affect social relationships but also impact emotional development and self-identity formation. These findings imply that educational institutions and counseling practitioners should develop intervention programs focusing on restoring a sense of safety, enhancing self-confidence, and building healthy interpersonal relationships through sustained social support and counseling services.